Adaptive Management: Learning and Action Approaches to Implementing Norms-shifting Interventions - McLarnon, Courtney; Gayles, Jennifer; Deepan, Prabu (USAID / Passages, 2021)
What Passages has Learned about Adaptive Management: • Be reflective about information that is collected and create a culture of learning. • Be systematic about establishing monitoring and learning systems. • Be strategic about data sources and analysis, prioritizing areas for learning and addressing issues raised. • Be inclusive about information collection: who is collecting what, how, and how is it being used.

Implementing adaptive management: A front-line effort — Is there an emerging practice? - Teskey, Graham; Tyrrel, Lavinia (Working Paper, 2021)
Among the many principles that currently inform donor-funded development initiatives, three appear to stand out: they should be politically informed, locally led, and adaptive. There is as yet little practical guidance for aid implementers regarding how to operationalise these approaches. What will it take to shift practice away from linear and planned approaches, towards models which foster local leadership and which engage with emergent and complex systems? This paper suggests that the answer is not to throw out the discipline of the logical framework, results frameworks, or theories of change. Rather they need to be handled rather more reflectively and ‘elastically’. The purpose of this paper is to set out how this can be achieved, and to propose 15 tools for donors, implementors and front-line staff to apply adaptive management (AM) in practice, at critical stages of the project cycle and within the dominant aid paradigm. This is what we are calling PILLAR: politically informed, locally led and adaptive responses. We are framing PILLAR to cover the full project cycle (design, implementation and review), hence the nomenclature of an ‘end to end’ approach. Our hope is that these tools will eventually replace the current planned, log-frame driven and top-down approach to aid design and delivery which dominates the development sector.

Value for money and adaptive programming - Approaches, measures and management - Laws, Ed; Valters, Craig (ODI, 2021)
- The United Kingdom’s Foreign, Commonwealth and Development Office (FCDO)’s standard economy, efficiency, effectiveness/cost-effectiveness and equity (4E) framework is still relevant for approaching, measuring and managing value for money (VfM) for adaptive programmes. • However, this framework needs to be reframed to capture and incentivise flexibility, learning and adaptation. • VfM appraisal and reporting should be done in a way that draws on beneficiary feedback and informs good decision-making, rather than just being a compliance exercise. • If VfM appraisal and reporting cannot be done appropriately for adaptive programmes, it should be avoided or minimised. There is a risk of diverting time and resources from more suitable tools and methods.

Opportunities and challenges for DAC members in ‘adapting to context’ - Sharp, Samuel; Wild, Leni (2021)
Key Messages New principles for OECD DAC members on ‘Managing for Sustainable Development Results’ emphasise tailoring result management approaches to different contexts; balancing internal compliance with empowerment at ground level; and adapting implementation in the pursuit of long-term outcomes. However development organisations face numerous challenges in aligning with these principles in practice. Reporting and evidence collection processes do not consistently encourage adaptive practice, reflecting their orientation towards accountability over learning. Context analysis is common during programme design, but used less on an ongoing basis. Popular tools –such as logical frameworks and theories of change - are often intepreted in linear ways, not as ‘living documents’ that react and change over time. Organisations need to meaningfully empower staff to work adaptively, including examining incentives and cultures that can make staff more comfortable with traditional results management. Even when senior leadership is supportive of adaptive ways of working, they can lack a clear understanding of the resourcing required and appropriate governance and management processes. Development organisations and their partners have attempted to address these challenges through the use of different monitoring and evaluation tools and methods, changes to reporting frameworks and templates, and initiatives to create positive incentives and motivate staff, leadership and partners at different levels.
Keywords: _tablet

LearnAdapt: a synthesis of our work on adaptive programming with DFID/FCDO (2017–2020) - Laws, Ed; Pett, Jamie; Proud, Emma; Rocha Menocal, Alina (Briefing Note, 2021)
Key takeaways. • Development is not linear or straightforward, but rather complex, uncertain and context-specific. This calls for international development actors to work differently, in ways that are based on deliberate experimentation, learning and adaptation, to inform decisions and drive effective development. • Although it might go by different names, adaptive programming has been used in a variety of areas and fields in both the public and private sectors. Development practitioners have much to learn from and contribute to these different approaches and experiences. • Trust and relationship-building across all relevant stakeholders are among the most critical enabling factors for adaptive management. They are essential to give partners the space, autonomy and authority needed to try, test, reflect, iterate and feed back at the frontline of implementation, and to give donors the confidence that decisions are being made on the basis of evidence and learning to improve effectiveness. • There is an urgent need to rethink how accountability requirements, results frameworks, value for money considerations, performance markers, procurement and contracting mechanisms and other processes are understood and applied so that they are better aligned with and can support adaptive management more effectively. • The role of senior managers leading adaptive programmes from the donor side should be to create a space for experimentation and learning. Funders should hold their partners accountable for learning and how it feeds into effective programming, rather than for delivering on predetermined targets. • While formal guidance is important, leadership, champions, institutional incentives, a supportive management culture and appropriate mindsets are essential to encourage adaptive ways of working. • Adaptive management is resource-intensive. It requires skill, commitment, time for building trust and investments in learning. It is a journey, not an immediate destination – so it calls for patience, open-mindedness and a more nuanced approach to risk.

A top Toolkit on Adaptive Management. But is that a good idea? – FP2P - Green, Duncan (From Poverty to Power, 2021)

How to do Adaptive Management in 15 easy steps – from a top new toolkit – FP2P - Green, Duncan (From Poverty to Power, 2021)

Learning to adapt & adapting to learn - Using elements of outcome mapping in the ‘Resilient Adolescents in the Syria Crisis’ programme - van Ongevalle, Jan; Kvintradze, Ana; Rennesson, Gaël; Miller, David (Save the Children, 2021)
This learning paper highlights how elements of outcome mapping were used by Save the Children Sweden in a project (2018-2020) that supports adolescents, affected by the Syria crisis, to become more resilient. The paper first outlines how the spheres of influence framework has been applied to develop an actor focused theory of change. It then describes how progress markers, as an alternative to SMART indicators, were formulated to monitor the programme’s results. The paper also outlines how long lists of progress markers were categorised in a more realistic and practical results framework. The paper then continues to elaborate how outcome journals, qualitative data analysis techniques and regular review meetings and reflection workshops were utilised for data collection, for collective learning among programme stakeholders and for informing planning and programme adjustment. Various practical guidelines and tips on how to implement elements of outcome mapping are provided. The final part of the paper explores to what extent outcome mapping was able to foster several key enablers of adaptive programme management and highlights some of the challenges that programme stakeholders faced. Practical recommendations towards the use of outcome mapping in future programmes are also proposed.

Adaptive Learning Guide: A pathway to stronger collaboration, learning, and adapting - Ross, Joey; Karlage, James; Etheridge, James; Alade, Mayowa; Fifield, Jocelyn; Goodwin, Christian; Semrau, Katherine; Hirschhorn, Lisa (USAID MOMENTUM Knowledge Accelerator, 2021)
The purpose of this Adaptive Learning Guide is to provide MOMENTUM project teams with the information and resources to integrate adaptive learning into the design, implementation, and improvement of MNCH/FP/RH programs. This guide provides a conceptual introduction to adaptive learning using links to existing resources and real-world examples of how adaptive learning can drive continuous learning and improvement in project work. The guide is built upon three foundational assumptions: We work in dynamic, often unpredictable environments. Unexpected turns of events will occur. Progress is rarely, if ever, linear. Integrating the principles and practices of USAID’s Collaborating, Learning, and Adapting Toolkit into projects and initiatives requires designing for learning and adaptation. We intend the guide to serve as a “starting point” for interested individuals and teams to begin or strengthen the processes that support the integration of adaptive learning into project work.

Technical assistance: a practical account of the challenges in design and implementation - Nastase, Alexandra; Rajan, Alok; French, Ben; Bhattacharya, Debarshi (Gates Open Research, 2021)
Technical assistance is provided to country governments as part of international development programmes to support policymaking or strengthen state capability. This article presents the conceptual evolution of ‘technical assistance’ linked to capacity development, starting with programmes aiming exclusively to enhance individual capacity in the 1950s to 1970s and progressing to complex systems approaches in the past ten years. It also presents some of the frequent challenges in designing and implementing technical assistance, drawing from the existing literature and the authors’ experience in international development. The article summarises the latest thinking about delivering more effective development, including the adaptive management practices and the initiatives to strengthen evidence about what works. Finally, we complement this article with a follow-up open letter reflecting on the current policy options and opportunities for change.

What have we learned about learning? Unpacking the relationship between knowledge and organisational change in development agencies - Yanguas, Pablo (German Development Institute / Deutsches Institut für Entwicklungspolitik (DIE), 2021)
Development cooperation has spent decades wrangling over the merits, evidence, and implications of what we may term “the learning hypothesis”: the idea that increased knowledge by development organisations must logically lead to increased effectiveness in the performance of their development activities. Organisations of all stripes have built research and monitoring and evaluation (M&E) departments, adopted a multitude of knowledge management systems and tools, and tinkered with different ways to structure their organograms to stimulate knowledge sharing and learning. The topic of organisational learning is particularly significant as the global development community grapples with increasingly complex problems and the aspiration of evidence-based policymaking. This paper presents an analytical framework for interrogating “the learning hypothesis”, breaking it down into causal steps: knowledge causes learning, learning causes organisational change, change causes effectiveness. The framework focuses on the first two sub-hypotheses, mapping out the conceptual space around them by outlining potential relationships between different types of knowledge – tacit and explicit, internal and external – and between different types of learning – operational and strategic. This map provides a foundation for three key research questions: What impact has the rising knowledge agenda had on development organisations? Which factors appear to enable or inhibit organisational learning? What is the relationship between operational and strategic learning and organisational change? A review of available evaluations and studies, including two cases from former UK Department for International Development (DFID) and the World Bank, reveals that there is insufficient evidence to support the causal claim that knowledge leads to learning and thereby to organisational change in development agencies. Sources point to tacit learning prevailing while explicit knowledge management systems flounder, and external advocacy agendas appear more compelling than internal research and evaluation products. It is not entirely clear how, or indeed, whether operational and strategic learning intersect, with delivery-level lessons hardly aggregating into structural or policy shifts. Organisational change – even that aimed at enhancing learning – is rarely based on lessons learned from practice. More research is necessary to fully unpack the learning hypothesis, but what limited evidence is available disproves rather than confirms its central claim. This has significant implications for the future of learning in development agencies as advocated by thought leaders, researchers, and reformers. In particular, the latter should consider an evidence-based reassessment of the function and value-for-money of research and M&E in development practice, and a more critical examination of the politics of external advocacy efforts around innovative aid approaches like thinking and working politically, adaptive management, or results-based management.

Peer reviews - Guidance for facilitators and participants - Wadley, Ian (Mediation Practice Series, 2021)
Essential points for practitioners and donors • Mediation offers a cost-effective and proven method for resolving armed conflict. Between 1985 and 2015, 75 per cent of armed conflicts in the world were resolved through agreement rather than by force. In most cases these processes will have involved third party facilitation or support. • Professional mediators understand the high stakes involved in their work to prevent, mitigate and resolve armed conflict. In addition, they and their financial supporters are increasingly required to demonstrate ‘value-for-money’ to ensure continued funding. • However, traditional monitoring and evaluation (M&E) methods are not well suited to this task, typically imposing artificially linear project models on a dynamic conflict situation, as well as compliance reporting that moves attention away from real value. • Traditional M&E methods tend to focus on documenting the past and generating vast amounts of data, rather than enabling timely adaptation of the project in the present. • Traditional M&E approaches rely heavily on external evaluation consultants. Even in the best of cases this may interfere with the mediation process and impose a heavy time burden on the project team, leading to low acceptance of traditional M&E approaches by mediation practitioners. • In contrast, an ideal M&E approach for mediation should deliver useful insights in even the most dynamic and sensitive mediation environments, impose a light reporting burden, and be readily accepted by mediation teams. It should protect discretion and trust, enable rapid adaptation, and also provide some assurance that donor funds are being well spent.

Thinking and working politically: What have we learned since 2013 - Teskey, Graham (TWP Community of Practice, 2021)
The Thinking and Working Politically (TWP) Community of Practice (CoP) was established at a small meeting tacked on at the end of a meeting of Governance Advisers working for the United Kingdom’s Department of International Development (DFID) on South and South-East Asian countries, held in Delhi in November 2013. Since then, a number of meetings have been held throughout the world, each addressing different issues; ‘TWP’ has entered the lexicon of mainstream development; the CoP has expanded to more than 300 people; a Washington DC chapter has been established; and the International CoP has been granted modest funding from DFID’s successor, the Foreign, Commonwealth and Development Office (FCDO) and from Australia’s Department of Foreign Affairs and Trade (DFAT). It is legitimate to ask, however, what has been achieved operationally: how have the ideas underpinning TWP affected operational practice? This short paper traces the evolution of the idea and practice of TWP from 2013 to late 2021, and identifies what we have learned. What has been successful, and what has not? I asked in 2017 whether TWP had become a second orthodoxy (Teskey, 2017). Did this represent hubris or was 2017 in some ways the apogee of what might rather grandly be called the TWP ‘movement’?